Management-Focused Health Informatics Research and Education at the University of Manchester - Peel, V. J. (Methods of Information in Medicine, 1994)
The Health Services Management Unit was established in 1956 and the Centre for Health Informatics in 1988 as one of eight new centres of research and professional practice. New programmes of informatics education have been created to integrate many of the areas of social and management sciences with clinical work. The model, of a multi-disciplinary higher education department based at a University with very substantial departments of Bio-Medicine and Computation, enables the Centre to reflect an alternative paradigm of health informatics. Informatics practitioners from many disciplines are taught a combination of knowledge and skills through a range of educational methods. A classification scheme for educational work is offered.
Keywords: Health Informatics; Education